Eradication and Sensitization of Methicillin Resistant Staphylococcus aureus to Methicillin with Bioactive Extracts of Berry Pomace - Salaheen, Serajus; Peng, Mengfei; Joo, Jungsoo; Teramoto, Hironori; Biswas, Debabrata (Frontiers in Microbiology, 2017)
The therapeutic roles of phenolic blueberry (Vaccinium corymbosum) and blackberry (Rubus fruticosus) pomace (commercial byproduct) extracts (BPE) and their mechanism of actions were evaluated against methicillin resistant Staphylococcus aureus (MRSA). Five major phenolic acids of BPE, e.g., protocatechuic, p. coumaric, vanillic, caffeic, and gallic acids, as well as crude BPE completely inhibited the growth of vegetative MRSA in vitro while BPE+methicillin significantly reduced MRSA biofilm formation on plastic surface. In addition, BPE restored the effectiveness of methicillin against MRSA by down-regulating the expression of methicillin resistance (mecA) and efflux pump (norA, norB, norC, mdeA, sdrM, and sepA) genes. Antibiogram with broth microdilution method showed that MIC of methicillin reduced from 512 µg/mL to 4 µg/mL when combined with only 200 µg Gallic Acid Equivalent (GAE)/mL of BPE. Significant reduction in MRSA adherence to and invasion into human skin keratinocyte Hek001 cells were also noticed in the presence of BPE. BPE induced anti-apoptosis and anti-autophagy pathways through overexpression of Bcl-2 gene and down-regulation of TRADD and Bax genes (inducers of apoptosis pathway) in Hek001 cells. In summary, novel and sustainable prophylactic therapy can be developed with BPE in combination with currently available antibiotics, especially methicillin, against skin and soft tissue infections with MRSA.